Composition, Texture, and Weathering Controls on the Physical and Strength Properties of Selected Intrusive Igneous Rocks from Northern Pakistan - Muhammad Yasir; Waqas Ahmed; Ihtisham Islam; Muhammad Sajid; Hammad Tariq Janjuhah; George Kontakiotis (Geosciences, 2022)
This study examines the mineralogy, texture, and weathering grades of intrusive igneous rocks from northern Pakistan, as well as their impacts on physical and strength properties. In comparison to felsic rocks, mafic and intermediate rocks have lower cumulative proportions of quartz, feldspar, and plagioclase, as well as higher specific gravity, strength (i.e., UCS and R-value), and UPV values. Similarly, samples with anhedral grain shapes, irregular boundaries, and fine to medium grain sizes (UD, ANS, and CGN) exhibited greater strength values, with compressive strengths of 121, 118, and 91 MPa and tensile strengths of 11, 9, and 12 MPa, respectively. The physical and strength properties of the investigated samples corresponded well with the weathering grades assigned to them, such as fresh (WG-I), slightly weathered (WG-II), and highly weathered (WG-III). That is, as the grade increased from WG-I to WG-III, the porosity and water absorption increased (0.28% and 0.72%, respectively), whereas the specific gravity, compressive strength, and tensile strength decreased (2.04, 20, and 2.5 MPa, respectively, for CGA). Although the presence of quartz impacts rock strength, no significant association was found between the strength and the maximum and mean grain sizes of other minerals.